Impact evaluation of SLM options to achieve land degradation neutrality: Dryland Systems interim report. - Le, Quang Bao; Bonaiuti, Enrico; Thomas, Richard (2017)
The aim of the project is to develop and implement a web-based GIS tool for defining sustainable land management (SLM) options by social-ecological context at global scale. This Global Geo-informatics Context and Options (GeoCOs) tool aims to support the implementation of SLM practices by the international community. The GeoCOs is designed to provide stakeholders/projects and programmes with plausible, robust extrapolation domains for guiding decisions on SLM options, and an open platform for docking different disciplinary projects into integrative/holistic, converging actions for SLM. The alpha version of the tool has been developed within 6 months of the project's initiation and is ready for testing with partners in March 2017 to achieve output 2, a country-specific knowledge base of standardized geo-referenced SLM options by context compendium